2021
DOI: 10.1097/aog.0000000000004436
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine for Acute Tocolysis of Preterm Labor

Abstract: Personal or nonessential information may be redacted at the editor's discretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Treatment of preterm labor is based on the inhibition of uterine contractions. Nifedipine is one of the most preferred tocolytic agents [14][15][16]. Unlike the previous study that states that there was a risk of placental hypoperfusion and maternal hypotension from decreased uterine blood flow due to the vasodilation effect it has on smooth muscles, this effect was confirmed in two recent studies [17,18].…”
Section: Discussionmentioning
confidence: 81%
“…Treatment of preterm labor is based on the inhibition of uterine contractions. Nifedipine is one of the most preferred tocolytic agents [14][15][16]. Unlike the previous study that states that there was a risk of placental hypoperfusion and maternal hypotension from decreased uterine blood flow due to the vasodilation effect it has on smooth muscles, this effect was confirmed in two recent studies [17,18].…”
Section: Discussionmentioning
confidence: 81%
“…Generating such information for clinicians can help to address the current gap between nifedipine maternal and fetal exposure and neonatal outcomes. 2,4,51 In conclusion, a detailed mechanistic PBPK model has been developed in this work to predict the maternalplacental-fetal PK of nifedipine. The model can provide insight into the nifedipine placental and fetal exposure helping to better understand the mechanisms of nifedipine distribution and elimination within the fetalplacental unit.…”
Section: Discussionmentioning
confidence: 99%
“…Nifedipine has been extensively used in the treatment of mild to severe hypertension for pregnant women and as a tocolytic agent to prevent preterm labor. [2][3][4] Twenty-seven years have passed since then and there are still many questions to be answered on this topic. Administering nifedipine during pregnancy is believed to carry varying levels of teratogenic risks.…”
mentioning
confidence: 99%
“…When event numbers are small, the degree of certainty around them is diminished, and this is reflected in wide confidence intervals (CI). For example, in a recent small randomized trial of 90 participants randomized to nifedipine or placebo for management of preterm labor, 17 the investigators reported a relative risk of delivery before 37 weeks of 1.1 (95% CI: 0.7-1.7). The 95% CI demonstrates that the true point estimate is most likely to be somewhere between 0.70 and 1.7, which represents anywhere from a 30% reduction in preterm birth rates, to almost a 2-fold increase in rates.…”
Section: Overcoming Challenges: Composite and Surrogate Outcomes Imba...mentioning
confidence: 99%